Limited influence of basalt weathering inputs on the seawater neodymium isotope composition of the northern Iceland Basin - Morrison, Rachel; Waldner, Astrid; Hathorne, Ed; Rahlf, Peer; Zieringer, Moritz; Montagna, Paolo; Colin, Christophe; Frank, Norbert; Frank, Martin (Chemical geology, 2019)
Radiogenic neodymium (Nd) isotopes have been widely used as a proxy for tracing present and past water masses and ocean circulation, yet relatively few data exist for seawater from the important deep water formation area around Iceland. We have analyzed the dissolved seawater Nd isotope compositions (expressed as ƐNd) of 71 seawater samples, as well as Nd concentrations [Nd] of 38 seawater samples, collected at full water column profiles from 18 stations in the shelf area off the southern coast of Iceland. The goal of this work was to determine to what extent weathering inputs from Icelandic basalts, which are characterized by a distinctly radiogenic ƐNd signature within the North Atlantic, contribute to the Nd isotope and concentration signatures of water masses in the northern Iceland Basin. Radiogenic ƐNd values of up to −3.5 and elevated concentrations of up to 21pmol/kg compared to nearby open ocean sites were found in surface waters at shallow sites closest to shore and to river mouths of Iceland. This documents partial dissolution of highly radiogenic basaltic particles, which are transported northwards by the coastal currents. A comparable signal is not observed, however, in offshore surface waters likely as a result of the advection of surface currents mainly directed onshore, thus isolating these sites from Icelandic weathering contributions. The dominance of Subpolar Mode Waters and Intermediate Water unaffected by Icelandic contributions in the offshore study area is supported by unradiogenic ƐNd signatures between −15 and −12. In agreement with hydrographic data, highly radiogenic bottom waters at one site on the Iceland-Faroe Ridge (ƐNd=−7.5) reveal the presence of almost pure Iceland Scotland Overflow Water (ISOW) near its formation site further to the east. In bottom waters of all deeper offshore sites, the combination of depleted Nd concentrations and similar ƐNd values (averaging at ≃−11.75 for the R/V Poseidon data and ≃−11 for the R/V Thalassa data) confirms the rapid entrainment of Atlantic mid-depth and deep waters into the overflow waters, which is accompanied by near bottom Nd removal via particle scavenging. Overall, our findings demonstrate that at present, apart from the radiogenic isotope signature of ISOW itself, the direct contribution of radiogenic Nd originating from weathering of Iceland basalts to the water column of the Iceland Basin is limited. This supports the reliable application of ƐNd values to trace changes in the mixing of open North Atlantic water masses (including ISOW). This article is part of a special issue entitled: “Cycles of trace elements and isotopes in the ocean - GEOTRACES and beyond” - edited by Tim M. Conway, Tristan Horner, Yves Plancherel, and Aridane G. González.
Available online 19 November 2018
Gesehen am 21.08.2019